2012
DOI: 10.1159/000337485
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine Reduces Nitric Oxide Donor-Mediated Dilation of Arterioles by Activating the Vascular Renin-Angiotensin System and Reactive Oxygen Species

Abstract: Introduction: We tested the hypothesis that asymmetric dimethylarginine (ADMA) interferes with other mechanisms in addition to inhibition of nitric oxide synthase (NOS). Thus, in skeletal muscle arterioles, in the presence of ADMA, we investigated the dilator effect of an NO donor and increases in flow and aimed to elucidate the underlying mechanisms, including the role of oxidative stress, which is known to reduce the bioavailability of NO. Methods and Results: In isolated rat gracilis skeletal muscle arterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Only a few studies have investigated the relation between ADMA and ACEIs. Veresh et al showed that ADMA activates the renin-angiotensin-aldosterone system (RAAS), which leads to vasoconstriction and increased oxidative stress (19). Moreover, Ito et al found reduced ADMA levels among hypertensive patients after being treated with ACEIs (20).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have investigated the relation between ADMA and ACEIs. Veresh et al showed that ADMA activates the renin-angiotensin-aldosterone system (RAAS), which leads to vasoconstriction and increased oxidative stress (19). Moreover, Ito et al found reduced ADMA levels among hypertensive patients after being treated with ACEIs (20).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reduced asymmetric dimethylarginine (ADMA) concentration in SHR treated with nebivolol, a third-generation β -blocker, has been associated with endothelial NO synthase (eNOS) agonist properties and increased bioavailability of NO [32]. In addition, ADMA has been shown to increase ROS level in arterioles in vitro by activation of the vascular renin-angiotensin system [35]. In our study, we showed that SOSA, which includes low-molecular weight antioxidant (scavengers) and superoxide dismutase, increased as a result of treatment with esmolol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies established that asymmetric dimethylarginine (ADMA), being a false substrate limits the activity of endothelial nitric oxide (NO) synthase thus production of NO. In addition, our previous studies and others revealed that elevated levels of ADMA elicits the release of reactive oxygen species (ROS) by activation of the renin angiotensin system (RAS) leading to vascular dysfunction [ 18 20 ]. ADMA can accumulate due to enhanced production or reduced catabolism and excretion [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ADMA has been identified as a risk factor for endothelial dysfunction and was shown to accelerating the progression of several cardiovascular diseases [ 23 ]. Thus, ADMA may serve as a biomarker indicating reduced bioavailability of NO [ 18 20 ]. Previous studies have shown that ADMA is partly excreted by the kidneys, and suggested that low urinary ADMA level predicts impaired cardiac function [ 24 ].…”
Section: Introductionmentioning
confidence: 99%